2002
DOI: 10.1001/archpsyc.59.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Impaired Cortical Inhibition in Schizophrenia Using Transcranial Magnetic Stimulation

Abstract: These results suggest that schizophrenia is associated with deficits in CI and that antipsychotic medications may increase CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
184
6
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 284 publications
(222 citation statements)
references
References 66 publications
22
184
6
10
Order By: Relevance
“…Although robust changes in cortical GAD67 mRNA are not typically found in the PFC of individuals with depression (Thompson et al, 2009;Sibille et al, 2011), significant decreases in somatostatin suggest that interneuron deficits may be especially prominent in a subset of interneurons shown to directly contribute to cortical plasticity (Lazarus and Huang, 2011). As inhibitory interneuron deficits are shared among those with depression, bipolar disorder, and schizophrenia (Thompson et al, 2009(Thompson et al, , 2011Fung et al, 2010;Hashimoto et al, 2008;Daskalakis et al, 2002), cortical plasticity deficits would also be expected to be found in multiple forms of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Although robust changes in cortical GAD67 mRNA are not typically found in the PFC of individuals with depression (Thompson et al, 2009;Sibille et al, 2011), significant decreases in somatostatin suggest that interneuron deficits may be especially prominent in a subset of interneurons shown to directly contribute to cortical plasticity (Lazarus and Huang, 2011). As inhibitory interneuron deficits are shared among those with depression, bipolar disorder, and schizophrenia (Thompson et al, 2009(Thompson et al, , 2011Fung et al, 2010;Hashimoto et al, 2008;Daskalakis et al, 2002), cortical plasticity deficits would also be expected to be found in multiple forms of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the methods presented in this paper can be used to directly evaluate inhibition from specific cortical regions (eg, DLPFC) whose dysfunction has been associated with the pathophysiology leading to several neurological and psychiatric disorders. For example, it has previously been demonstrated that unmedicated patients with schizophrenia have impaired CI, and that such inhibitory deficits can be rectified through treatment with antipsychotic medications (Daskalakis et al, 2002a;Fitzgerald et al, 2002). However, these studies were limited by the fact that such findings were from the motor cortex, a cortical region that is perhaps less relevant to the pathophysiology of schizophrenia compared with the DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage to recording inhibition directly from the cortex, however, will be that future source localization studies may uncover the origins of such inhibitory potentials. We anticipate that such future work will also be invaluable in helping to identify the pathophysiological origins of a variety of disorders associated with disrupted CI (Cantello et al, 2002;Daskalakis et al, 2002a). In this regard, future pharmacological studies and molecular studies attempting to clarify the link between these EEG recordings of LICI to GABA B receptor-mediated mechanisms in the cortex are needed.…”
Section: Discussionmentioning
confidence: 99%
“…From circumstantial evidence of an association of schizophrenia with a lowered threshold for seizures, 40 recent studies have found direct evidence of impaired cortical inhibition (i.e. enhanced excitability), 41 and reduced transcortical inhibition of motor circuitry. 42 Studies of molecular markers of GABA signaling in post-mortem brain of patients with schizophrenia have provided consistent evidence of diminished GABA activity.…”
Section: Introductionmentioning
confidence: 99%